Synthesized Geopolymers Adsorb Bacterial Proteins, Toxins, and Cells - Popovich, John; Chen, Shaojiang; Iannuzo, Natalie; Ganser, Collin; Seo, Dong-Kyun; Haydel, Shelley E. (Frontiers in Bioengineering and Biotechnology, 2020)
Pore-forming and hemolytic toxins are bacterial cytotoxic proteins required for virulence in many pathogens, including staphylococci and streptococci, and are notably associated with clinical manifestations of disease. Inspired by adsorption properties of naturally-occurring aluminosilicates, we engineered inexpensive, laboratory-synthesized, aluminosilicate geopolymers with controllable mechanical properties, porosity, and surface characteristics to remove pathogenic or cytotoxic material from the surrounding environment. In this study, macroporous and mesoporous geopolymers were produced with and without stearic acid surface modifications that increase hydrophobicity. Geopolymer binding efficacies were assessed by measuring adsorption of methicillin-resistant Staphylococcus aureus (MRSA) culture filtrate proteins, α-hemolysin and streptolysin-O toxins, MRSA whole cells, and antibiotics. Macroporous and mesoporous geopolymers were strong nonselective adsorbents for bacterial protein, protein toxins, and bacteria. Although some geopolymers adsorbed antibiotics, these synthesized geopolymers could potentially be used in nonselective adsorptive applications and optimized for adsorption of specific biomolecules.